Kisapmata - De Leon, Mike; Lacap, Rodt; Hernando, Cesar; Ilustre, Lorrie; Reyes, Ramon; Navarro, Jess; Del Mundo, Clodualdo; Villavicencio, Raquel; Ongpin, Simon; Concio, Charo Santos-; Atienza, Rolando S.; Silayan, Vic; et al. (Bancom Audiovision, 1981)
Sgt. Diosdado Carandang (Vic Silayan), a patriarch who carries more than mere fatherly love to his daughter, is the ultimate personification of evil here. Unable to accept to accept the impending marriage of his daughter (Charo Santos) to beau Noel Manalansan (Jay Ilagan), he makes life miserable for the pair. Ilagan, slowly learns the hideous secret the family carries and despite his plight, is unable to stop it.